Devising a comprehensive methodology for estimating the economic efficiency of implementing an investment project for ensuring energy security of enterprises: organizational-economic aspect - Prokhorova, Viktoriia; Budanov, Mykola; Budanov, Pavlo; Zaitseva, Anna; Slastianykova, Anzhelika (Eastern-European Journal of Enterprise Technologies, 2025)
The subject of this study is the process of assessing the economic efficiency of implementing an investment project aimed at ensuring the energy security of enterprises within the power sector at the microeconomic level. The task considered was to devise a comprehensive and adaptive approach to assessing the economic efficiency of investments, enabling effective planning, implementation, and adjustment of the investment project for ensuring energy security at enterprises under uncertainty. The research revealed that conventional approaches, such as cost-benefit analysis, do not adequately account for risks and potential threats that arise during the implementation of investment projects. An improved comprehensive method for assessing economic efficiency has been proposed, consisting of eight key stages that are interconnected based on calculations and analysis of the economic efficiency indicators of the investment project for the enterprise. A distinctive feature of this method is the integration of quantitative and qualitative indicators of investment projects, which allows for evaluating their effectiveness and ensuring real-time adaptation to justify management decisions under uncertainty. The choice of criteria for evaluating investment objects for forming a system of energy security indicators for enterprises has been substantiated. A computational algorithm was developed to monitor the dynamics of indicator changes, which helps make timely management decisions to minimize energy security risks. The practical significance of this study is that it provides enterprises with methodological foundations for optimizing investment strategies. It has been shown that maximum energy security and financial benefits for enterprises are achieved through the complete prevention of accidents, ensuring profitability at the level of 41 %